Supporting recovery in patients with psychosis through care by community-based adult mental health teams (REFOCUS): a multisite, cluster, randomised, controlled trial. (June 2015) - Slade, Mike; Bird, Victoria; Clarke, Eleanor; Le Boutillier, Clair; McCrone, Paul; Macpherson, Rob; Pesola, Francesca; Wallace, Genevieve; Williams, Julie; Leamy, Mary
Summary: Background: Mental health policy in many countries is oriented around recovery, but the evidence base for service-level recovery-promotion interventions is lacking. Methods: We did a cluster, randomised, controlled trial in two National Health Service Trusts in England. REFOCUS is a 1-year team-level intervention targeting staff behaviour to increase focus on values, preferences, strengths, and goals of patients with psychosis, and staff–patient relationships, through coaching and partnership. Between April, 2011, and May, 2012, community-based adult mental health teams were randomly allocated to provide usual treatment plus REFOCUS or usual treatment alone (control). Baseline and 1-year follow-up outcomes were assessed in randomly selected patients. The primary outcome was recovery and was assessed with the Questionnaire about Processes of Recovery (QPR). We also calculated overall service costs. We used multiple imputation to estimate missing data, and the imputation model captured clustering at the team level. Analysis was by intention to treat. This trial is registered, number ISRCTN02507940. Findings: 14 teams were included in the REFOCUS group and 13 in the control group. Outcomes were assessed in 403 patients (88% of the target sample) at baseline and in 297 at 1 year. Mean QPR total scores did not differ between the two groups (REFOCUS group 40·6 [SD 10·1] vs control 40·0 [10·2], adjusted difference 0·68, 95% CI −1·7 to 3·1, p=0·58). High team participation was associated with higher staff-rated scores for recovery-promotion behaviour change (adjusted difference −0·4, 95% CI −0·7 to −0·2, p=0·001) and patient-rated QPR interpersonal scores (−1·6, −2·7 to −0·5, p=0·005) at follow-up than low participation. Patients treated in the REFOCUS group incurred £1062 (95% CI −1103 to 3017) lower adjusted costs than those in the control group. Interpretation: Although the primary endpoint was negative, supporting recovery might, from the staff perspective, improve functioning and reduce needs. Implementation of REFOCUS could increase staff recovery-promotion behaviours and improve patient-rated recovery. Funding: National Institute for Health Research.